Synthesis and evaluation of various heteroaromatic benzamides as analogues of –ylidene-benzamide cannabinoid type 2 receptor agonists. Issue 36 (5th September 2019) - Moir, Michael; Boyd, Rochelle; Gunosewoyo, Hendra; Montgomery, Andrew P.; Connor, Mark; Kassiou, Michael
Graphical abstract: The synthesis of a small library of heteroaromatic benzamides as potential cannabinoid type 2 receptor agonists is described. Highlights: Synthetic routes to access heterocyclic benzamides are developed. Functional activity at the cannabinoid receptors is evaluated. Ylidene benzamide moiety is determined to be imperative for activity. Abstract: The CB2 receptor is an attractive target for the treatment of a wide range of diseases and pathological conditions. Compounds that selectively activate the CB2 receptor are desirable as this avoids CB1 -mediated psychoactive effects. Heteroarylidene-benzamides have demonstrated efficacy as selective CB2 receptor agonists. We aimed to expand the structure-activity relationship studies of this series of compounds by investigating the heteroaromatic core via the synthesis and in vitro evaluation of a small library of various heteroaromatic benzamide analogues. As heteroaromatic amides are privileged scaffolds in drug design, methods to synthesise them are of interest. Concise and reliable synthetic strategies were developed to access these novel analogues. The –ylidene-benzamide moiety is shown to be essential for CB activity as all amide derivatives exhibit no functional activity at either CB2 or CB1 receptors.